Stowaways in the cargo: Contaminating nucleic acids in rAAV preparations for gene therapy - Mark A. Brimble; Stephen M. Winston; Andrew M. Davidoff (2023)
Recombinant AAV (rAAV) is the most used delivery vector for clinical gene therapy. However, many issues must be addressed before safer and more widespread implementation can be achieved. At present, efficacies are highly variable across trials and patients, and immune responses after treatment are widely reported. Although rAAV is capable of directly delivering gene-encoded therapeutic sequences, increased scrutiny of viral preparations for translational use have revealed contaminating nucleic acid species packaged within rAAV preparations. The introduction of non-therapeutic nucleic acids into a recipient patient adds to the risk burden, immunogenic or otherwise, of rAAV therapies. DNA from incomplete expression cassettes, portions of plasmids or vectors used to facilitate viral replication, and production cell line genomes all have the potential to be packaged within rAAV. Here, we review what is currently known about the profile, abundance, and post-treatment consequences of nucleic acid impurities within rAAV and cover strategies that have been developed to improve rAAV purity. Furthering our understanding of these aberrantly packaged DNA species will help to ensure the continued safe implementation of rAAV therapies as the number of patients treated with this modality increases.